Artificial Intelligence (AI) Usage In Today’s Teaching And Learning Process: A Review - Aisyah Nurjanah; Irma Nuraeni Salsabila; Adelia Azzahra; Riska Rahayu; Nina Marlina (Syntax Idea)
In today's technology world, the integration of artificial intelligence (AI) has become increasingly prominent in education, with enormous potential to improve the teaching and learning experience. AI, defined by its ability to imitate human intelligence, possesses enormous power and has the potential to dramatically impact a variety of areas, most notably education. AI has significantly improved learning experiences for both teachers and students by allowing them to be customized and personalized. This review article investigates the prospects provided by AI in modern teaching and learning processes, with a special emphasis on its advantages in language learning. This study examines existing literature and studies on AI in education, with a focus on language learning environments. The results show AI's advantages in giving targeted feedback and practice opportunities, making language learning easier, and improving overall learning efficiency and effectiveness. Thus, this review contributes to a better understanding of AI's role in redefining present educational paradigms, as well as its potential to transform teaching and learning methodologies.